Pengurangan Pemborosan Dan Perbaikan Pada Kegiatan Proses Prepare Delivery Dengan Menggunakan Metode Seven Waste Di Pt Inoac Polytechno Indonesia - Sutaarga, Ossa; Mas’ud, Sony Wijaya (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2024)
PT Inoac Polytechno Indonesia is a private company engaged in manufacturing, especially in the manufacture of foam mattresses, furniture products, and automotive interior products. In the process of preparing for childbirth there are still many things or activities that cause waste, such as repetitive activities and the use of manual tools. One method that can be used to reduce waste in manufacturing is by identifying seven wastes. In changing the work system from a manual to an automated system, it is carried out based on WEB using PHP (Hypertext Preprocessor) programming to reduce the waste that occurs in the finishgood warehouse. In one day PT. Inoac Polytechno Indonesia can deliver goods +-32 trucks/day. If with a manual system, the shipping preparation process takes 37 minutes/PO (Purchase Order), with an automated WEB-based system, the target is that the shipping preparation process takes 30 minutes/PO (Purchase Order). The time needed for one time process to prepare delivery before repairs are carried out is 37 minutes/PO (purchase order). Whereas after the repairs were carried out, the time needed in one prepare delivery process was 31 minutes/PO (purchase order). Keywords: Process Prepare Delivery, Seven Waste, Delivery Control Board, PAM, Lean Manufacturing